Effects of high-altitude training on adaptation in swimming athletes before competition: analysis with compressed spectral array electroencephalogram - Lin, L.; Zhang, L.; Li, J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The aim of high-altitude training before competition is to obtain maximum hypoxia physiological adaptation, through training in a hypoxic environmental at high altitude. Therefore, the aim of this investigation was to determine the effects of high altitude training on the ability of self-regulation at the angle of compressed spectral array (CSA) and electroencephalogram (EEG) in swimming athletes before competition. Methods Nine elite swimming athletes were selected from the Guangdong Swimming Team from March to April in 2001. The subject group included 8 male athletes: 1 female athlete. Two athletes were ranked highly internationally and 7 athletes were ranked highly nationally. Observations were made prior to altitude training and after two weeks, followed by another data collection at four weeks. The purpose of collecting this information was to determine the bodies ability to adapt to the reduction of oxygen in the air. CSA and EEG were detected with Beijing Rijiang electron RJTB-1 high-rank sport training state (brain) monitor apparatus. Results After high-altitude training, the average frequency of brain information distribution was higher than before high-altitude training. Pre and post altitude training differences were statistically significant. Conclusions Cerebral order measurements of the athletes provided data to suggest multi-centralization, which in turn suggests that lack of oxygen creates changes in brain function to which the body adapts. Effects of high-altitude training and maintenance of the adaptations have proven ineffective. Upon return to land it is difficult to maintain the intensity with a normal amount of oxygen.